Pengaruh Tebal Film Aspal terhadap Kinerja Campuran Bergradasi FAA Berdasarkan Variasi Ukuran Maksimum Agregat - Ratna Yuniarti; Rohani Rohani; Hasyim Hasyim; Made Mahendra; Fera Fitri Salsabila (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2026)
Flexible pavements at airports must be designed to withstand heavy and repeated aircraft loadings. Therefore, the hot mix asphalt for airport flexible pavements must comply with the specifications outlined in the FAA Advisory Circular AC 150/5370-10. This study evaluated the effect of asphalt film thickness on the mechanical properties of FAA-graded mixtures with three maximum aggregate sizes: 25, 19, and 12.5 mm. The analysis concluded that the maximum aggregate size in FAA gradations plays a role in determining the surface area covered by asphalt and the resulting asphalt film thickness. Asphalt film thickness significantly influenced the Marshall value, flow, and Marshall Quotient. A thicker asphalt film results in a higher retained stability index, indicating that the mixture is more capable of withstanding stripping. Gradation with a smaller maximum aggregate size results in a thinner asphalt film, making the asphalt layer more susceptible to damage owing to water penetration. The test of the mixture's resistance to water immersion through indirect tensile strength showed that the TSR value for the three variations of the maximum aggregate size met the FAA standard, which was greater than 75%.